Bioaccumulation of thallium by the wild plants grown in soils of mining area - Sasmaz, Merve; Akgul, Bunyamin; Yildirim, Derya; Sasmaz, Ahmet (Taylor & Francis Inc, 2016)
Gumuskoy Ag (As, Pb, and Tl) deposits are one of the largest silver deposits in the country and located about 25km west of Kutahya, Turkey. This study investigated the accumulation and transport of thallium into 11 wild plants in soil of the mining area. Plant samples and their associated soils were collected from the field and Tl contents were measured with inductively coupled plasma mass spectroscopy (ICP-MS). The mean concentrations in the soil, roots, and shoots of the studied plants were, respectively, 170, 318, and 315mgkg(-1) for Tl. The plants analyzed and collected from the studied area were separated into different groups based on enrichment coefficients of roots and shoots (ECR and ECS). The results showed that because of their higher ECR and ECS, the following could be good bioaccumulators: CY, IS, SL, and VR for Tl. Therefore, these plants can be useful for remediation or phytoremediation of soils polluted by Tl.
Keywords: Thallium; uptake; wild plants; phytoremediation; mining area